A Hybrid Dynamic Voltage Sharing Scheme for Series-connected SiC MOSFETs with Single Gate Drive. Issue 1 (1st December 2022) - Ren, Yuhan; Wang, Jinhao; Meng, Runquan; Li, Tingting; Chen, Juan; Zhang, Taotao
Abstract: At present, the voltage level of a commercial SiC MOSFET can hardly meet the requirements of high-voltage field. For the sake of achieving the application of MOSFETs in high-voltage fields, the method of series-connected MOSFETs has become a practical and effective solution. However, multiple series-connected SiC MOSFETs face the problem of voltage unbalance, especially dynamic voltage unbalance. Generally, the problem of dynamic unbalance could be solved using load side voltage sharing schemes or the methods of gate side. This paper uses a hybrid dynamic voltage sharing scheme for the single-driven series-connected SiC MOSFETs. That is to say, based on a sequential lagging single gate drive topology, combining active clamping circuits with RCD snubber circuits are introduced to solve the problem of dynamic voltage unbalancing of the whole module in this paper. Compared to the circuit without any dynamic voltage sharing scheme, the dynamic voltage imbalance degree of the circuit with a hybrid dynamic voltage sharing scheme is decreased to 3.75% during the switching-on and switching-off periods. The equalization effect would be verified through the simulation under clamped inductive load in LTspice.